2016
DOI: 10.1093/infdis/jiw243
|View full text |Cite
|
Sign up to set email alerts
|

ModA2 Phasevarion Switching in NontypeableHaemophilus influenzaeIncreases the Severity of Experimental Otitis Media

Abstract: Several human-adapted bacterial pathogens use a phasevarion (ie, a phase-variable regulon) to rapidly and reversibly regulate the expression of many genes, which include known virulence factors, yet the influence of phasevarion-mediated regulation in pathogenesis remains poorly understood. Here we examine the impact of the nontypeable Haemophilus influenzae (NTHI) ModA2 phasevarion on pathogenesis and disease severity in a chinchilla model of experimental otitis media. Chinchillas were challenged with NTHI var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 28 publications
(42 reference statements)
4
50
0
Order By: Relevance
“…Brockman et al subsequently found that the phasevarion impacted disease progression and severity in a chinchilla model of NTHi-induced experimental OM. A shift in the phasevarion status, or an epigenetic switch, significantly increased disease severity compared to a genetically identical population that did not shift phasevarion status [61]. The phasevarion was also shown to regulate NTHi biofilm formation under various disease specific conditions.…”
Section: Regulation and Adaptationmentioning
confidence: 95%
See 1 more Smart Citation
“…Brockman et al subsequently found that the phasevarion impacted disease progression and severity in a chinchilla model of NTHi-induced experimental OM. A shift in the phasevarion status, or an epigenetic switch, significantly increased disease severity compared to a genetically identical population that did not shift phasevarion status [61]. The phasevarion was also shown to regulate NTHi biofilm formation under various disease specific conditions.…”
Section: Regulation and Adaptationmentioning
confidence: 95%
“…The chinchilla has been utilized in studies of in-host microbial adaptation with NTHi with respect to the phasevarion [48,61] or nutritional limitation [63]. The infectivity of wild type and mutant NTHi [44] and pneumococcal [18,25] strains have been compared effectively in the chinchilla model.…”
Section: Infection Studiesmentioning
confidence: 99%
“…Examples of such evasion mechanisms include coexisting viral infections resulting in a negative pressure buildup in the Eustachian tube, exaggerated cytokine production leading to increased inflammation, and a build‐up of mucin, which decreases mucociliary clearance and hence results in OM infections that are less likely to be cleared (Table ) . Bacteria are even able to manipulate their gene expression through phase variation and interact with other pathogens, increasing their virulence and decreasing the chances of host clearance . Immunologic evasion is multifactorial, and often depends on damage to the host mucociliary tract, genetic regulatory changes within otopathogens, the number as well as a variety of different otopathogens that have colonized the nasopharynx, and finally, the delicate interplay between the host's adaptive and innate immune response (Table ).…”
Section: Immunologic Evasionmentioning
confidence: 99%
“…Besides mucin, many bacterial pathogens are also able to use phase variation to regulate gene expression and evade potent host immune responses (Fig. ), though researchers are still attempting to better elucidate this phenomenon . NTHi, in particular, has various forms of phase variation such as rearrangement and modification of glycosyltransferase genes, allele on/off switching of N 6 ‐adenine DNA methyltransferase (ModA), and manipulation of the polythymidine (poly‐T) tract in the hia promoter .…”
Section: Immunologic Evasionmentioning
confidence: 99%
See 1 more Smart Citation